2009
DOI: 10.1016/j.jpeds.2008.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Multiple Environmental Exposures and Glutathione S-transferase P1 on Persistent Wheezing in a Birth Cohort

Abstract: Objective-To determine the impact of environmental exposures (diesel exhaust particle (DEP), environmental tobacco smoke (ETS), and mold) that may contribute to oxidative stress on persistent wheezing in the Cincinnati Childhood Allergy and Air Pollution Study (CCAAPS) birth cohort and to determine how the impact of these exposures is modified by the GST-P1 Ile105Val polymorphism.Study design-A land-use regression model was used to derive an estimate of each child's DEP exposure. ETS exposure was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 30 publications
4
46
1
1
Order By: Relevance
“…Visible mould exposure Wheeze Of the nine publications evaluating the longitudinal effect of early exposure to visible mould at home and wheezing in the first 3 yrs of life, seven studies observed a significant positive association [8,12,36,41,42,48,49]. In one US birth cohort study (the Cincinnati Childhood Allergy and Air Pollution Study) from IOSSIFOVA et al [8], the reported increase in risk was persistent from 1-3 yrs of age.…”
Section: Resultsmentioning
confidence: 99%
“…Visible mould exposure Wheeze Of the nine publications evaluating the longitudinal effect of early exposure to visible mould at home and wheezing in the first 3 yrs of life, seven studies observed a significant positive association [8,12,36,41,42,48,49]. In one US birth cohort study (the Cincinnati Childhood Allergy and Air Pollution Study) from IOSSIFOVA et al [8], the reported increase in risk was persistent from 1-3 yrs of age.…”
Section: Resultsmentioning
confidence: 99%
“…Children who were homozygous (+/+) or heterozygous (−/+) for GSTM1 (or GSTT1) were classified as GSTM1 (GSTT1) positive, and those who were homozygous deleted (−/−) were classified as GSTM1 (GSTT1) null. Modification of the association between acetaminophen and wheeze by the presence of the minor allele in GSTP1 (ie, Ile/Val or Val/Val) was evaluated based on (1) previous associations with asthma11 13 and (2) altered conjugation kinetics of toxicants related to asthma among individuals with this genotype 15…”
Section: Methodsmentioning
confidence: 99%
“…30 High diesel exhaust particles increase the risk for wheezing only in children with the GSTP1 rs 1695 G allele. 31 Our finding that prenatal exposure to home renovation elevated CB IgE levels in neonates with GSTP1 G or NRF2 A alleles from atopic mothers suggests that prenatal exposure to home renovation may induce T-cell differentiation to Th2 through oxidative stress. Interestingly, the finding that gene-environment interactions are only present in the offspring from atopic mothers suggests that the maternal atopic status may modify the interactions between genetic polymorphisms of reactive oxygen specifies and prenatal exposure to home renovation through another interaction with atopy-related genes of neonates inherited from atopic mothers or via the intrauterine environment provided by atopic mothers.…”
Section: Discussionmentioning
confidence: 79%